Interface conditions of roughness-induced superoleophilic and superoleophobic surfaces immersed in hexadecane and ethylene glycol - Li, Yifan; Pan, Yunlu; Zhao, Xuezeng (Beilstein Journal of Nanotechnology, 2017)
Interface conditions are an important property that can affect the drag of fluid flow. For surfaces with different oleophobicity, the boundary slip at the solid–oil interface is mostly larger than that at the solid–water interface. Roughness is a key factor for the wettability of superoleophilic/superoleophobic surfaces, and it has been found to affect the effective value of slip length in measurements. Moreover, there are no studies on the effect of roughness on slip at interfaces between oil and superoleophilic/superoleophobic surfaces. A theoretical description of the real surface roughness is yet to be found. Results show that the effective slip length is negative and decreases with an increasing root mean squared (RMS) roughness of surfaces, as the increasing roughness enhances the area with discontinuous slip at the solid–liquid interface. The underlying mechanisms are analyzed. The amplitude parameters of surface roughness could significantly inhibit the degree of boundary slip on both superoleophilic surfaces in Wenzel state and superoleophobic surfaces in Cassie state immersed in oil. The oleic systems were likely to enhance boundary slip and resulted in a corresponding reduction in drag with decreasing roughness on the solid–oil interfaces.
Keywords: boundary slip; roughness; superoleophilic; superoleophobic

Springer Handbook of Nanotechnology - Bhushan, B. (Springer, 2010)

(untitled) - Navier, C. L. M. H. (Mem. Acad. Sci. Inst. Fr., 1823)

(untitled) - Wolynes, P. G.; Deutch, J. M. (J. Chem. Phys., 1976)

(untitled) - Watanabe, K.; Udagawa, Y.; Udagawa, H. (J. Fluid Mech., 1999)

(untitled) - Shirtcliffe, N. J.; McHale, G.; Newton, M. I.; Zhang, Y. (ACS Appl. Mater. Interfaces, 2009)

(untitled) - Tretheway, D. C.; Meinhart, C. D. (Phys. Fluids, 2002)

(untitled) - Bonaccurso, E.; Kappl, M.; Butt, H.-J. (Phys. Rev. Lett., 2002)

(untitled) - Cottin-Bizonne, C.; Steinberger, A.; Cross, B.; Raccurt, O.; Charlaix, E. (Langmuir, 2008)

(untitled) - Zhu, L.; Attard, P.; Neto, C. (Langmuir, 2011)

(untitled) - Pan, Y.; Bhushan, B.; Zhao, X. (Beilstein J. Nanotechnol., 2014)

(untitled) - Pan, Y.; Jing, D.; Zhao, X. (Sci. Adv. Mater., 2017)

(untitled) - Jing, D.; Bhushan, B. (J. Colloid Interface Sci., 2015)

(untitled) - Jing, D.; Pan, Y. (Int. J. Heat Mass Transfer, 2016)

(untitled) - Jing, D.; Pan, Y.; Wang, Y. (Int. J. Heat Mass Transfer, 2017)

(untitled) - Pit, R.; Hervet, H.; Léger, L. (Phys. Rev. Lett., 2000)

(untitled) - Schmatko, T.; Hervet, H.; Léger, L. (Langmuir, 2006)

(untitled) - Zhu, Y.; Granick, S. (Phys. Rev. Lett., 2002)

(untitled) - Bonaccurso, E.; Butt, H.-J.; Craig, V. S. J. (Phys. Rev. Lett., 2003)

(untitled) - Guriyanova, S.; Semin, B.; Rodrigues, T. S.; Butt, H.-J.; Bonaccurso, E. (Microfluid. Nanofluid., 2010)

(untitled) - Kunert, C.; Harting, J. (Phys. Rev. Lett., 2007)

(untitled) - Li, Y.; Bhushan, B. (Soft Matter, 2015)

(untitled) - McHale, G.; Newton, M. I. (J. Appl. Phys., 2004)

(untitled) - Sbragaglia, M.; Benzi, R.; Biferale, L.; Succi, S.; Toschi, F. (Phys. Rev. Lett., 2006)

(untitled) - Lund, N. J.; Zhang, X. P.; Mahelona, K.; Hendy, S. C. (Phys. Rev. E, 2012)

(untitled) - Blanchard, D.; Ligrani, P. (Phys. Fluids, 2007)

(untitled) - Lee, T.; Charrault, E.; Neto, C. (Adv. Colloid Interface Sci., 2014)

(untitled) - Vinogradova, O. I.; Yakubov, G. E. (Phys. Rev. E, 2006)

(untitled) - Craig, V. S. J.; Neto, C.; Williams, D. R. M. (Phys. Rev. Lett., 2001)

(untitled) - Brown, P. S.; Bhushan, B. (Sci. Rep., 2015)

Handbook of Chemistry and Physics - Haynes, W. M. (Academic Press, 2015)

Instruction to tribology - Bhushan, B. (Wiley, 2002)